2010
DOI: 10.1021/es902852v
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Photochemistry of Fluoroquinolone Antibiotics: Kinetics, Pathways, and Multivariate Effects of Main Water Constituents

Abstract: The ubiquity of fluoroquinolone antibiotics (FQs) in surface waters urges insights into their fate in the aqueous euphotic zone. In this study, eight FQs (ciprofloxacin, danofloxacin, levofloxacin, sarafloxacin, difloxacin, enrofloxacin, gatifloxacin, and balofloxacin) were exposed to simulated sunlight, and their photodegradation was observed to follow apparent first-order kinetics. Based on the determined photolytic quantum yields, solar photodegradation half-lives for the FQs in pure water and at 45 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
150
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(162 citation statements)
references
References 53 publications
10
150
0
2
Order By: Relevance
“…Results indicated that increasing nitrate concentration did not significantly accelerate the removal of SPY in water. It is acknowledged that in nature waters nitrate is the primary source of hydroxyl radical Å OH, and molecular probes like methanol and isopropanol are usually employed to determine Å OH (Zhou and Mopper, 1990;Brezonik and Fulkerson-Brekken, 1998;Ge et al, 2010). Experimental results by adding isopropanol to the solution revealed that Å OH seemingly did not contribute to the SPY degradation under the conditions in this study, since there was no significant alternation for improving the photodegradation of SPY (Fig.…”
Section: Nitrate Ionmentioning
confidence: 72%
See 1 more Smart Citation
“…Results indicated that increasing nitrate concentration did not significantly accelerate the removal of SPY in water. It is acknowledged that in nature waters nitrate is the primary source of hydroxyl radical Å OH, and molecular probes like methanol and isopropanol are usually employed to determine Å OH (Zhou and Mopper, 1990;Brezonik and Fulkerson-Brekken, 1998;Ge et al, 2010). Experimental results by adding isopropanol to the solution revealed that Å OH seemingly did not contribute to the SPY degradation under the conditions in this study, since there was no significant alternation for improving the photodegradation of SPY (Fig.…”
Section: Nitrate Ionmentioning
confidence: 72%
“…Antibiotics are a class of commonly used PPCPs used as human and veterinary medicine. Due to their pseudo-persistent nature and potential to cause antibiotic resistant bacteria and genes (Baran et al, 2006;Zhang et al, 2013;Guo et al, 2013), it is imperative to study the fate and transport of antibiotics and their impacts in the natural environment (Ge et al, 2009(Ge et al, , 2010Guo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, UV-254 photodegradation has been investigated for the removal of some emerging contaminants such as PPCPs (Benitez et al, 2013;Canonica et al, 2008;Liu et al, 2011;Marotta et al, 2013). In addition, reactive oxygen species (ROS) including singlet oxygen ( 1 O 2 ), superoxide anion radical ðO À$ 2 Þ and even stronger oxidant hydroxyl radical ( OH) can be photogenerated by certain PPCPs (Agrawal et al, 2007;Chen et al, 2008;Ge et al, 2010;Inbaraj et al, 2002), indicating that photodegradation could be a promising technology for the removal of emerging contaminants like fluconazole. However, there has been no photodegradation report available for fluconazole.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Fasani et al (2008) expected linezolid as well as all drugs bearing an aminofluorophenyl substituent to be photolabile and possibly phototoxic in a similar manner to fluoroquionolones. In the case of the antibacterial class of fluoroquinolones, photodegradation processes have also been described previously (e.g., Garcia-Käufer et al 2012;Ge et al 2010;Prabhakaran et al 2009;Sturini et al 2012). These authors, however, did not study the environmental relevance nor the (eco)toxicity of the PTPs.…”
Section: Biodegradationmentioning
confidence: 86%